Inibição da secreção pulsátil de hormônio luteinizante e função gonadal em ratos obesos: papel dos neurônios KNDy - Laísa Taline Magalhães Hipólito (2018)
Obesity reduces luteinizing hormone (LH) secretion and causes infertility in men. In the past few years, it has been proposed that kisspeptin (Kp) is the central peptide responsible for connecting metabolic information and the reproductive axis. The KNDy neurons of the arcuate nucleus of the hypothalamus (ARC) coexpress Kp, neurokinin B (NKB) and dynorphin (Dyn). Here, we evaluated the pulsatile LH secretion in obese male rats and investigated the role of KNDy neurons in obesity-induced suppression of the hypothalamic-pituitary-gonadal axis (HPG). In experiment 1, weaning rats were treated with high-fat-diet (HFD) or standard diet (CT) for 13 weeks. HFD rats displayed higher caloric intake, increased body weight and oxygen consumption when compared with CT. Moreover, HFD rats displayed higher adiposity index, Lee index and glucose intolerance compared with CT. For pulsatile LH secretion measurement, serial blood samples were collected from the tail tip (10 uL every 6 minutes) during 3 h, which revealed reductions of 50% in pulse amplitude and 36% in mean LH concentrations in HFD rats compared to the CT, whereas the pulse frequency did not differ between groups. After the last blood sampling, some of the rats were perfused and the brains were processed for immunohistochemistry. The other part of the rats was decapitated and the brains were processed for real-time PCR (q-PCR). The number of Kp-immunoreactive (ir) neurons in the ARC was 35% lower in HFD rats compared with CT. In addition, HFD rats displayed lower Nkb expression in the ARC. The preoptic area (POA) showed decreased Gnrh1 expression and the pituitary lower mRNA levels of GnRH receptor and LH-β subunit in HFD rats. In experiment 2, we investigated whether intracerebroventricular (i.c.v.) treatment with kisspeptin-10 (Kp-10) would restore the pulsatile LH secretion in HFD rats. Indeed, icv Kp-10 treatment increased the amplitude of LH pulses and mean LH concentrations in CT and HFD rats. In experiment 3, CT and HFD rats from experiment 2 were castrated for evaluation of LH hypersecretion in response to orchiectomy. As expected, LH levels were elevated in CT CAST rats. On the other hand, LH increase in response to orchidectomy was greatly diminished in HFD CAST. In addition, the number of Kp-ir neurons in the ARC was 40% lower in HFD CAST rats compared with CT CAST. In experiment 4, rats were treated with HFD for 18 weeks. From the eighth week on, HFD rats received Kp-10 daily (HFD+Kp 1 nmol or 3 nmol/rat/day s.c.) or saline (HFD+S). The CT group received only saline (CT+S). Treatment with s.c. Kp-10 was not able to restore the HFD-induced suppression of LH pulse amplitude or mean LH concentrations. On the other hand, the treatment with 3 nmol Kp-10 was able to revert the defective testosterone secretion in HFD rats. The results demonstratethat HFD-induced obesity inhibits the amplitude of LH pulses, which is associated with of Kp peptide and Nkb mRNA in KNDy neurons. Central injection of Kp-10 is able to restore the HFD-induced suppression in LH pulsatile release. On the other hand, chronic treatment with low doses of s.c. Kp-10 did not show the same effect. However, 3 nmol of Kp-10 appears to exert an effect on testicular steroidogenesis independent from gonadotrophin release, suggesting an alternative mechanism of Kp action at the testicular level.